Valores hematológicos em Geochelone carbonária (Jabuti) - Bergamini, Bruno Carvalho da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Hematology has a great importance in assessing the health of all animals, including reptiles, since it aids in the diagnosis of certain diseases and help to monitor patient's clinical evolution, although studies and articles in this area are rare, even with the increasing number of calls of these animals in veterinary clinics. Moreover, there are a lot of environmental and individual factors, which influence the hematological values of this group, such as age, sex, stress levels, nutrient levels and season which the exam was made, among others. For these reasons studies that aimed to evaluate the reference values of some specie, are essential to increase the knowledge in the field and to assist on the clinical approach. This paper aim’s to study the patterns of Hematology of Tortoise (Geochelone carbonaria) seeking the greater knowledge of clinical pathology of this species and increasing the possibilities for diagnosis, monitoring clinical outcome, and assessment of the general state and treatment

O exame hematológico tem grande importância na avaliação da saúde de dos animais, inclusive dos repteis, pois auxilia no diagnóstico de algumas enfermidades e ajuda a acompanhar a evolução clinica do paciente, porém os trabalhos e artigos referentes a estes assuntos são escassos, mesmo com o crescente número de atendimentos destes animais nas clinicas veterinárias. Além disso, existe uma grande quantidade de fatores individuais e ambientais, que influenciam nos valores hematológicos, como a idade, sexo, níveis de estresse, níveis nutricionais e estação do ano em que se faz o exame, entre outros. Por estes motivos estudos que tem como objetivo avaliar os valores de referência em animais clinicamente normais, são fundamentais para aumentar o conhecimento e auxiliam a abordagem clinica Este trabalho procurou determinar os padrões Hematológicos do Jabuti (Geochelone carbonária) visando maior conhecimento da clínica desta espécie e ampliação das possibilidades de diagnóstico, acompanhamento da avaliação do estado geral e tratamento
Keywords: Hematologia veterinaria; Animais silvestres; Veterinary hematology